The Role of Artificial Intelligence in Decision Making: Improving E-Commerce Business Efficiency and Innovation - Efendi, Regina Pinkan; Qolbi, Ihfada; Afandi, Syifa Zahra Arista; Kusumasari, Indah Respati; Nugroho, Rusdi Hidayat (Jurnal Bisnis dan Komunikasi Digital, 2025)
This research aims to analyze the role of Artificial Intelligence (AI) in decision-making within e-commerce businesses, focusing on its impact on efficiency, innovation, and competitive advantage. This study employs a qualitative approach using literature review to explore the implementation of AI in e-commerce. AI enables real-time analysis of large-scale data, supporting more efficient and accurate strategic decision-making. The technology also fosters innovation through features such as recommendation systems and the integration of augmented reality (AR) and virtual reality (VR), enhancing customer experiences. Furthermore, AI strengthens companies' competitiveness by personalizing services and leveraging big data to design superior strategies. The findings show that AI not only improves operational efficiency and innovation but also serves as a key element for business sustainability in the digital era.